The Impact of Antarctic Treaty Challenges on the US Military - Bridley, Ryan J.; Matthews, Kevin W. (The US Army War College Quarterly: Parameters, 2023)
While the Antarctic Treaty of 1961 largely prevented conflicts on the continent, growing challenges to the treaty system could affect the United States and the global community. Through historical documents and press reports, this article examines ice deterioration, unreported and unregulated fishing, resource extraction preparation, hostilities between treaty members, and the roles of China and Russia in the region. It provides recommendations for policymakers and military strategists on how the United States can maintain global security and treaty interests—and the potential request for intervention—within the guidelines of the National Security Strategy.